Pemodelan dan Perancangan Data Penyusunan Soal Ujian Pada Perguruan Tinggi - Miwan Hidayat (LPPM Universitas Bina Sarana Informatika, 2022)
Examination is an evaluation stage for students to find out the achievement of the competency level that has been determined in the Semester Learning Plan document. With the implementation of the exam, it can be seen the level of mastery of student competencies that are expected to be in accordance with certain subjects. To support the process of preparation, examination, approval and archiving of exam questions in universities, a system for preparing exam questions is needed that is in accordance with the guidelines for preparing exam questions. This study aims to design a data model that can be used for the preparation of exam questions at universities according to Standard Operating Procedures in the implementation of the preparation of exam questions. The relational data model was chosen as a technique in solving research problems. Based on the results of the research that has been done, it can be concluded that data modeling and design can be applied to the data for preparing exam questions at universities using a relational data model that can be implemented in the MySQL Database Management System.